2018
DOI: 10.1007/s12630-018-1118-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output-based fluid optimization for kidney transplant recipients: a proof-of-concept trial

Abstract: www.clinicaltrials.gov (NCT02512731). Registered 31 July 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Two previous studies investigated a goal-directed fluid therapy during KT: 15 , 20 both Cavaleri et al 15 and Corbella et al 20 applied a Stroke Volume (SV) optimization protocol with different objectives. Cavaleri 15 aimed to show a reduction in early complications after KT using a FloTrac TM /EV1000 monitor, while Corbella 19 aimed to evaluate if the use of esophageal doppler monitoring would alter the amount of fluids given during KT.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies investigated a goal-directed fluid therapy during KT: 15 , 20 both Cavaleri et al 15 and Corbella et al 20 applied a Stroke Volume (SV) optimization protocol with different objectives. Cavaleri 15 aimed to show a reduction in early complications after KT using a FloTrac TM /EV1000 monitor, while Corbella 19 aimed to evaluate if the use of esophageal doppler monitoring would alter the amount of fluids given during KT.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, there is increasing interest in advanced hemodynamic monitoring in pediatric kidney transplantation. Especially, esophageal doppler monitoring seems to gain popularity in this field. Although it is still difficult to show an unambiguous impact on outcome, monitoring the effect of fluids, and vasopressor support on CO makes sense as a cornerstone in hemodynamic management.…”
Section: Discussionmentioning
confidence: 99%
“…25 Apparently, there is increasing interest in advanced hemodynamic monitoring in pediatric kidney transplantation. Especially, esophageal doppler monitoring 26 seems to gain popularity in this field. Although it is still difficult to…”
Section: Alternative Co-monitoringmentioning
confidence: 99%
“…The use of OD did not improve immediate graft function; however, the number of postoperative complications caused by fluid overload was limited [ 103 ]. Another study reported that OD did not alter the volume of fluid administered or the rate of complications in this group of patients [ 111 ].…”
Section: Intraoperative Carementioning
confidence: 99%